Anti-corona filling adhesive with low relative dielectric constant and preparation method
By developing anti-corrosion filler with low relative dielectric constant, the cross-linking technology of nano-SiO2 powder and epoxy adhesives was used to solve the problem of corona discharge of water-wheel generators in high altitude areas, and a better anti-corrosion effect was achieved.
Patent Information
- Application Number
- CN202510072142.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-26
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-04-26
AI Technical Summary
In high altitude areas, low air pressure and air density lead to a decrease in discharge voltage of the stator rod and winding surface of large-capacity water turbine generators, which in turn causes corona discharge problem. The existing anti-halo materials cannot effectively solve this problem.
A corona-proof filler with low relative dielectric constant was developed, and a corona-proof filler with excellent electrical properties was prepared by mixing nano SiO2 powder with an epoxy adhesive and crosslinking.
The anti-corrosion filler can effectively share the electric field that the air bears, reduce the possibility of air being broken down, reduce the risk of corona discharge, and significantly improve the anti-corrosion performance under high altitude conditions.
Smart Images

Figure CN119799240A_ABST
Abstract
Description
[0001] Divisional application This application is a divisional application based on the Chinese invention patent application with application number CN2024105249832, application date April 26, 2024, and invention name "Anti-corona glue and preparation method for high-altitude large-scale hydropower equipment". Technical Field
[0002] The invention belongs to the technical field of anti-corona of electromechanical equipment, and in particular relates to an anti-corona filling glue with a low relative dielectric constant and a preparation method thereof. Background Art
[0003] Corona refers to the phenomenon of local air ionization and current discharge caused by the electric field strength exceeding the air breakdown voltage near high-voltage power equipment or live conductors. Corona can cause serious damage to equipment. Corona discharge in motors is mainly caused by the uneven distribution of electric fields in certain parts of the winding insulation surface or excessive local field strength, which leads to the ionization of nearby air and causes glow discharge. It is a local discharge, and the small gaps between insulating fixed structural parts (pads, felts, etc.), between structural parts and stator wire rods, and surface burrs and other defects accelerate the occurrence and development of corona discharge. Long-term corona discharge is one of the main reasons for the destruction of the insulation layer of stator wire rods and even the final breakdown. It will eventually reduce the service life of the generator and pose a serious threat to the safe operation of the motor. In recent years, with the continuous increase in the rated capacity and rated voltage of generator sets, the prevention and control of corona in the stator windings of air-cooled motors represented by hydro-turbine generators has become a global technical problem that needs to be solved urgently. The construction and commissioning of hydropower generators in high-altitude and cold regions such as Tibet, Qinghai, and Xinjiang has increased rapidly in my country, and the industry has put forward higher requirements for the insulation technology of high-altitude units. This is because under high-altitude conditions, low air pressure and low air density will cause the surface corona discharge voltage of the stator bars and stator windings of large-capacity hydropower generators to decrease (that is, corona will begin to be generated when the normal operating voltage is not reached), making the anti-corona problem of the stator windings of large-capacity hydropower generators in this scenario more serious. Coating the equipment with an insulating layer is an important means to prevent corona.
[0004] The patent with the publication number CN103160183A and the invention name "Preparation method of nano anti-corona paint" discloses a nano anti-corona paint, whose ingredients include epoxy resin, organic montmorillonite, toluene or xylene, silicon carbide powder, etc. The mass of silicon carbide powder added in the patent is 3 to 4 times the mass of epoxy resin. The technical problem solved by the patent is mainly to improve the mechanical properties and heat resistance of anti-corona paint. The heat resistance grade of the anti-corona paint disclosed in the patent reaches Class F (155°C). However, such performance cannot meet the needs of use in extremely cold and wet weather conditions. The patent with the publication number CN108976991A and the invention name "A high-resistance anti-corona paint for high-voltage motor coils and its preparation method" discloses a high-resistance anti-corona paint, whose ingredients include epoxy resin, honeycomb silica nanotubes, polyamide resin, toluene or xylene, etc. The amount of honeycomb silica nanotubes added is less than 0.1%. The principle is that the hollow structure of the nanotubes has very good elasticity when shrinking and expanding slightly, so it can significantly improve the high and low temperature impact resistance of the high resistance anti-corona paint layer. However, this high resistance anti-corona paint cannot solve the problem of corona discharge of the stator windings of large-capacity hydro-turbine generators caused by low air pressure and air density, which leads to the reduction of surface discharge voltage of the stator bars and stator windings. In addition, the air density is low in high altitude areas, and the air is more easily broken down, that is, it is easier to corona and discharge.
[0005] In summary, it is necessary to develop anti-corona materials with low relative dielectric constants, which can share part of the electric field borne by the air, making the air less likely to be broken down and thus less likely to cause corona discharge. Summary of the invention
[0006] The object of the present invention is to provide an anti-corona filling glue with a low relative dielectric constant and a preparation method thereof, so as to partially solve or alleviate the above-mentioned deficiencies in the prior art. The present invention specifically adopts the following technical solutions.
[0007] On one hand, the present invention provides a novel anti-corona filling glue.
[0008] The invention discloses an anti-corona filling adhesive with a low relative dielectric constant. The anti-corona filling adhesive is prepared by mixing an epoxy adhesive and a filler. The epoxy adhesive comprises an A component and a B component. The filler is a nano-SiO2 powder. The nano-SiO2 powder is cross-linked with the epoxy adhesive A component. The epoxy adhesive A component is a bisphenol A type epoxy resin. The epoxy adhesive B component comprises a composite curing agent and a diluent. The composite curing agent comprises polyamide, phenolic amine, 2,4,6-tri(di- The invention discloses a novel epoxy adhesive comprising a polyamide component, a phenolic acid component and a phenolic acid component. The epoxy adhesive comprises a polyamide component, a phenolic acid component and a phenolic acid component. The polyamide component comprises ...
[0009] As a preferred embodiment, the composite curing agent consists of polyamide, phenalkamine and 2,4,6-tris(dimethylaminomethyl)phenol.
[0010] Furthermore, the chemical formulas of the components in the composite curing agent are as follows.
[0011] Polyamide; Phenolic amine (n=0,1,2…); 2,4,6-Tris(dimethylaminomethyl)phenol.
[0012] Among them, both polyamide and phenolic amine contain primary amines, which react with epoxy groups to form amines (reaction 1); amines further react with epoxy groups to form tertiary amines (reaction 2); 2,4,6-tris(dimethylaminomethyl)phenol contains tertiary amines, which react with hydroxyl groups to undergo etherification, ultimately causing the epoxy system to form a three-dimensional network structure (reaction 3), as follows.
[0013] .
[0014] As a preference, the weight percentage of the nano-SiO2 powder in the epoxy adhesive includes 1%, 1.5%, 2%, 2.5% or 3%.
[0015] It is understandable that the ratio of the epoxy adhesive component A to the component B is adjusted so that the viscosity of the colloid made of the epoxy adhesive component A and the component B is in the range of 180 to 380 mPa·s. Within this viscosity range and falling within the material ratio of the epoxy adhesive component A to the epoxy adhesive component B of 10:3, 3:1.5 or 3:2, all fall within the protection scope of the present invention. Among them, as a preferred embodiment, the mass ratio of the epoxy adhesive component A to the epoxy adhesive component B is 10:3.
[0016] As a preference, the mass ratio of the substances in the epoxy adhesive component B is 35:9:4:12 of polyamide:phenolic amine:2,4,6-tris(dimethylaminomethyl)phenol:diluent.
[0017] Furthermore, the particle size of the nano-SiO2 powder is in the range of 7-40 nm.
[0018] Furthermore, the specific surface area of the nano-SiO2 powder is 120 m 2 / g.
[0019] Another aspect of the present invention provides a method for preparing the novel anti-corona filling glue.
[0020] The method for preparing the anti-corona filling glue with low relative dielectric constant comprises the following steps: S01: Mix the nano-SiO2 powder and the epoxy adhesive component A and stir evenly to obtain a first mixed solution; S02: adding the epoxy adhesive component B to the first mixed solution and stirring evenly to obtain a second mixed solution, wherein the mass ratio of the epoxy adhesive component A to the epoxy adhesive component B includes 10:3, 2:1 or 3:2; and the weight percentage of the nano-SiO2 powder in the epoxy adhesive is 1%-3%; S03: placing the second mixed liquid in a vacuum drying environment, vacuuming to remove bubbles at room temperature, and then curing to obtain the anti-corona filling glue with a low relative dielectric constant.
[0021] Furthermore, in the S01, the nano-SiO2 powder and the epoxy adhesive component A are magnetically stirred at 60-80°C for 0.5-1h, and ultrasonically shaken to mix the components evenly.
[0022] Furthermore, in S02, the epoxy adhesive component B is added to the first mixed solution and magnetically stirred at room temperature for 10-15 minutes to obtain the second mixed solution.
[0023] Beneficial technical effects: The present invention provides a low relative dielectric constant ( εThe anti-corona filling glue provided by the present invention has a minimum ε is 4.31, which can effectively share part of the electric field borne by the air (the ε 1), so that the air is not easily broken down, and thus it is not easy to cause corona discharge. The anti-corona filling glue provided by the present invention was tested at altitudes of 2500m, 3000m, 3500m and 4000m. Under the conditions of 0℃ and 30℃, its local discharge amount was less than that of the control group, and its corona initiation voltage was higher than that of the control group, proving that it also has a good anti-corona effect in high-altitude areas with thin air. Furthermore, the electrical performance of the anti-corona filling glue was tested, proving that the anti-corona filling glue of the present invention has lower resistance and higher breakdown field strength than the control group.
[0024] The anti-corona filling glue provided by the present invention is mainly applied to the binding structure of the winding end of a large hydropower unit when used, and fills and covers the air gap and surface burrs at the binding site to improve the surface potential distribution of the winding, reduce the average field strength and maximum field strength distribution of the stator wire bar and the winding air gap, and inhibit the generation and development of corona. In particular, the electric field at the tip of the burr can be significantly reduced, thereby effectively reducing the discharge risk when the burr exists, and playing an anti-corona effect.
[0025] Finally, the preparation method provided by the present invention is simple and convenient, with controllable cost and good industrialization prospect. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. In all the drawings, similar elements or parts are generally identified by similar reference numerals. In the drawings, each element or part is not necessarily drawn according to the actual scale. Obviously, the drawings described below are some embodiments of the present invention. For those of ordinary skill in the art, other drawings can also be obtained based on these drawings without paying creative labor.
[0027] Figure 1 SEM images of the anti-corona filling glue containing different weight percentages of nano-SiO2 powder (a is 0.5wt%, b is 1wt%, c is 1.5wt%, d is 2wt%, e is 2.5wt%, f is 3wt%, scale bar is 1μm); Figure 2 The dielectric loss results of the anti-corona filling glue containing different amounts of nano-SiO2 powder added; Figure 3 This is the electric field distribution diagram under the ideal binding state in the simulation test; Figure 4This is the electric field distribution diagram when bubbles exist in the simulation test; Figure 5 This is the electric field distribution diagram when burrs exist in the simulation test; Figure 6 This is a test chart of the physical and chemical properties of the anti-corona filling glue (A is the flow time and kinematic viscosity, B is the drying time, C is the applicable period, and D is the overall shrinkage); Figure 7 This is the electrical performance test diagram of the anti-corona filling glue; Figure 8 Schematic diagram of the chemical reaction of the curing agent used in the present invention. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0029] Herein "and / or" includes any and all combinations of one or more of the associated listed items.
[0030] Herein, "plurality" means two or more than two, ie, it includes two, three, four, five, etc.
[0031] As used in this specification, the term "about" typically means + / - 5% of the stated value, more typically + / - 4% of the stated value, more typically + / - 3% of the stated value, more typically + / - 2% of the stated value, even more typically + / - 1% of the stated value, and even more typically + / - 0.5% of the stated value.
[0032] In this specification, some embodiments may be disclosed in a format of being in a range. It should be understood that this description of "being in a range" is only for convenience and brevity, and should not be interpreted as a rigid limitation on the disclosed range. Therefore, the description of the range should be considered to have specifically disclosed all possible sub-ranges and independent numerical values within this range. For example, the description of the range 1-6 should be considered to have specifically disclosed sub-ranges such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as individual numbers within this range, such as 1, 2, 3, 4, 5 and 6. Regardless of the breadth of the range, the above rules apply.
[0033] Example 1 This embodiment provides an example of a method for preparing a new type of anti-corona filling glue.
[0034] raw material: Epoxy adhesive component A: bisphenol A epoxy resin.
[0035] Epoxy adhesive component B: composite curing agent: polyamide (PA), phenalkamine (PAA), 2,4,6-tris (dimethylaminomethyl) phenol (DMP-30); diluent: resorcinol diglycidyl ether. The mass ratio of each substance is polyamide: phenalkamine: 2,4,6-tris (dimethylaminomethyl) phenol: resorcinol diglycidyl ether is 35:9:4:12.
[0036] Filler: Nano-SiO 2, Specific surface area 120m 2 / g, particle size 7-40nm.
[0037] Preparation method of anti-corona filling glue (hereinafter referred to as anti-corona glue): S01: After mixing the nano-SiO2 powder and the bisphenol A epoxy resin, magnetic stirring is performed at 60°C for 1 hour to cross-link the nano-SiO2 and the bisphenol A epoxy resin, and then ultrasonic vibration is performed for 1 hour to mix them evenly (no bubbles in the mixed liquid), to obtain the first mixed liquid.
[0038] S02: Add component B of the epoxy adhesive to the first mixed solution, and magnetically stir at room temperature for 10 minutes to obtain a second mixed solution, wherein component A is 3 kg and component B is 0.9 kg (mass ratio is 10:3).
[0039] S03: The second mixed liquid is placed in a vacuum drying oven, vacuumed at room temperature to remove bubbles, and then poured into a mold for curing. After curing at room temperature for 24 hours, the anti-corona filling adhesive sample for high-altitude large hydropower units is obtained. According to the different weight percentages of nano-SiO2 powder in the epoxy adhesive, sample 1 (0.5%wt), sample 2 (1%wt), sample 3 (1.5%wt), sample 4 (2%wt), sample 5 (2.5%wt), sample 6 (3%wt) and control sample (0%wt) are prepared respectively, where samples 1 to 5 are collectively referred to as experimental samples.
[0040] It is to be understood that the specific proportions of the various substances added in the above preparation method are only examples and not limitations.
[0041] How to use the anti-corona filling glue: The anti-corona filling glue prepared by the above method is applied to the binding structure of the winding ends of large hydropower units.
[0042] Example 2 This example provides key performance verification of the anti-corona filling glue prepared in Example 1.
[0043] 2.1 Dispersibility of nano-SiO2 powder in filler.
[0044] See Figure 1 . Figure 1 The scanning electron microscope (SEM) images of the anti-corona filling adhesive of samples 1-6 are shown in the figure. It can be seen that the dispersion of various added amounts of nano-SiO2 powder in the matrix epoxy adhesive (also called matrix adhesive) is relatively good, and no obvious agglomeration phenomenon is observed.
[0045] 2.2 Relative dielectric constant and dielectric loss test of anti-corona filling glue Relative dielectric constant: It is the main parameter that reflects the dielectric properties or polarization properties of piezoelectric material dielectric under the action of electrostatic field, usually expressed as ε In the presence of AC voltage, the distribution of electric field strength in the medium is related to the medium ε Therefore, it is usually desirable for the insulation material coated on the motor to have a smaller ε , so the electric field strength shared by the insulating material will be relatively large. ε is 1, the electric field strength will be greater, and the air breakdown field strength itself is low, so when the insulating material ε The smaller it is, the more it can share a part of the electric field borne by the air, making the air less likely to be broken down and thus less likely to cause corona discharge.
[0046] Dielectric loss: refers to the energy loss caused by the dielectric conductivity and dielectric polarization hysteresis effect of the insulating material under the action of the electric field, usually expressed as tan δ If the insulation material loss is large, the temperature of the insulation material will rise under the action of the electric field, causing the insulation material to age (become brittle, decompose, etc.). If the medium temperature continues to rise, it may even melt or burn the dielectric, lose its insulation ability, and eventually lead to thermal breakdown.
[0047] Test method: According to GB / T 1409-2006 Recommended method for measuring the dielectric constant and dielectric loss factor of electrical insulating materials at power frequency, audio frequency and high frequency. The results are shown in Table 1 and Figure 2 .
[0048] Table 1 Dielectric loss results of anti-corona filling glue with different nano-SiO2 powders added Calculation method of ε change rate: dielectric value of anti-corona glue with added SiO2 powder - dielectric value of anti-corona glue without added SiO2 powder / dielectric value of anti-corona glue without added SiO2 powder.
[0049] For example: Taking the case of adding 2.5wt% SiO2 powder as an example, the dielectric change rate = (4.31-4.76) / 4.76 = -9.45%.
[0050] Calculation method of tan δ change rate: dielectric loss value of anti-corona glue with added SiO2 powder - dielectric loss value of anti-corona glue without added SiO2 powder / dielectric loss value of anti-corona glue without added SiO2 powder.
[0051] For example, taking the addition of 2.5wt% SiO2 powder as an example, the dielectric loss change rate = (0.00759-0.00654) / 0.00654 = 16.06%.
[0052] Conclusion: The anti-corona glue with the lowest relative dielectric constant is the preferred one. Therefore, the experimental sample (sample 5) with 2.5wt% nano-SiO2 powder added and the control sample (EP) without SiO2 powder added were selected for subsequent tests.
[0053] 2.3 Simulation Test The simulation test is aimed at detecting the influence of anti-corona filling glue on the electric field at the binding structure of the hydropower unit winding end.
[0054] Simulation steps: (1) Build model; (2) Set material properties; (3) Set boundary conditions; (4) Mesh generation; (5) Solve.
[0055] (1) Model construction: Use SOLIDWORK to construct a three-dimensional model of the stator winding. Then import it into the COMSOL software and select the "Current" interface under the "AC / DC" module in COMSOL. Construct the air domain to obtain the stator winding simulation model.
[0056] (2) Setting material properties: Use the COMSOL built-in material library and the results of material performance tests to assign corresponding material properties to each structure in the simulation model, such as setting the relative dielectric constant and conductivity of the material.
[0057] (3) Setting boundary conditions: The copper busbar conductor of the middle wire rod is set as the high-voltage end, and a voltage of 19.8 kV is applied. The copper busbar conductors of the upper and lower wire rods and the low-resistance anti-corona layer boundary of the three wire rods are set as the grounding end, and a voltage of 0 V is applied.
[0058] (4) Mesh division: The copper busbar conductor and the main insulation layer adopt free tetrahedral mesh division, and the size is set to ultra-fine; the binding structure adopts a customized unit size, and the maximum unit size is 0.2 mm; the pad adopts a customized unit size, and the maximum unit size is 8 mm; the bubble and burr adopt a customized unit size, and the maximum unit size is 0.1 mm.
[0059] (5) Solution: Select the frequency domain solver as the solver, set the frequency study to 50 Hz, set the number of iterations to 1000, and the results of the COMSOL simulation developer should include potential, electric field, and loss, and the corresponding expressions are V, ec.normE, and ec.Qrh, respectively. The test results are shown in Table 2 and Figure 3-Figure 5 .
[0060] Table 2 Electric field results at the bubble and burr in the simulation test in conclusion: Figure 3 In the experiment, when the equipment end binding structure is in an ideal state, that is, it is assumed that there are no defects such as bubbles and burrs, the anti-corona glue of the control sample group and the anti-corona glue of the experimental sample group have similar effects on the electric field distribution of the binding structure. The electric field distribution of the binding structure is relatively uniform, without obvious distortion areas. The maximum field strength is at the corner position of the line rod and the pad. The electric field strengths of the anti-corona glue of the control group and the anti-corona glue of the experimental group are 1.24 kV / mm and 1.22 kV / mm, respectively. Figure 4 It shows that when bubbles exist, the electric field strength at the bubbles is significantly higher than that at other parts, but the increase is not large. The maximum electric field strength at the bubbles of the winding using the control sample is 1.68 kV / mm; the maximum electric field strength at the bubbles of the winding using the experimental sample is 1.60 kV / mm, which is reduced by about 4.76%. Figure 5 It can be seen that when burrs are present, the harm of burrs to windings is more serious. The maximum electric field strength of the winding using the control sample at the tip of the burr is 3.53 kV / mm, which has exceeded the breakdown field strength of air under normal conditions of 3 kV / mm, and there is a risk of discharge in the winding; the maximum electric field strength of the winding using the experimental sample at the tip of the burr is 2.49 kV / mm, which is about 29.37% lower. Obviously, the anti-corona glue with added SiO2 powder can effectively reduce the risk of discharge when burrs are present.
[0061] 2.4 Component screening of anti-corona filling glue Part 2.2 of this embodiment verifies that the dielectric constant of the anti-corona glue with 2.5wt% nano-SiO2 added is the lowest. The research and development team speculates that the dielectric constant of the anti-corona glue may be related to the viscosity of the anti-corona glue, and the viscosity of the anti-corona glue is determined by the material ratio of each component, so the components of the anti-corona glue are further screened and verified.
[0062] Table 3 Effect of adjustment of epoxy adhesive AB components on the performance of anti-corona adhesive Conclusion: Adjusting the A and B components of the epoxy adhesive will lead to changes in the matrix viscosity, and the change in the matrix viscosity will further lead to different interactions and dispersibility with nano-SiO2, thus affecting the relative dielectric constant of the final anti-corona adhesive. From the results in Table 3, when the matrix viscosity is too large, the relative dielectric constant ε of the final anti-corona adhesive is higher. When the matrix viscosity range is about 180~380 mPa·s, the relative dielectric constant ε of the anti-corona adhesive is lower; among them, the optimal mass ratio of the A and B components of the epoxy adhesive is 10:3.
[0063] Example 3 This example provides other performance verifications of the anti-corona filling glue prepared in Example 1.
[0064] 3.1 Physical and chemical properties of anti-corona filling glue Test method: The filling glue of sample 5 and the control sample was applied to the binding structure of the winding end of a large hydropower unit to fill and cover the air gap and surface burrs at the binding site. The physical and chemical properties of the two samples were tested. Figure 6 .
[0065] in conclusion: Figure 6 A shows that at the same test distance, the control sample (EP) has a lower kinematic viscosity and thus a shorter flow time, while the experimental sample has a higher viscosity and better retention. Figure 6 B shows that the control sample (EP) has a longer drying time, while the experimental sample has a shorter drying time, matching the viscosity results. Figure 6 C shows that the shelf life of the experimental samples is shorter. Figure 6 D shows that the total volume shrinkage of the experimental sample is smaller. The total volume shrinkage of the control sample (EP) is 4.39%, while the total volume shrinkage of sample 5 is 2.75%. The smaller total volume shrinkage of sample 5 indicates that the air gap and surface burrs at the binding can be better covered after the filling glue dries.
[0066] It is understood that the "usable period" of the present invention refers to the period from the time when the two-component epoxy adhesive is mixed to the time when it becomes gelled and cannot be used; the so-called gelling refers to the phenomenon that the adhesive changes from a liquid to a solid or semi-solid that cannot be used. The usable period test method used in the present invention is to put the epoxy adhesive into a container after it is prepared, and then place a stirring rod in the container, and slowly pull the stirring rod upward at a uniform speed. When the adhesive and the container can leave the table for more than 10 cm, the usable period ends.
[0067] 3.2 Electrical performance test of anti-corona filling glue Test method: The breakdown field strength is carried out in accordance with "GB / T 1408.1-2006 Test method for electrical strength of insulating materials Part 1: Test under power frequency"; the relative tracking index is carried out in accordance with "GB / T 4207-2022 Determination method for tracking resistance index and relative tracking index of solid insulating materials"; the resistivity is carried out in accordance with "GB / T 1410-2006 Test method for volume resistivity and surface resistivity of solid insulating materials", see Figure 7 .
[0068] Conclusion: In general, the performance of the experimental samples is similar to that of the control samples in terms of electrostatic index and resistivity, but the experimental samples have lower resistance and higher breakdown field strength, which reaches 65.37kV / mm, while the breakdown field strength of the control sample is 59.04kV / mm. This shows that the anti-corona filler with nano-SiO2 is less likely to be broken down.
[0069] 3.3 Insulation resistance test of anti-corona filling glue Test method: The test method is carried out in accordance with GB / T 20833.4-2021 Rotating Electric Machine Winding Insulation Part 4: Insulation Resistance and Polarization Index Measurement, the altitude is 2000m, and the test temperature is room temperature. The results are shown in Table 4.
[0070] Table 4 Insulation resistance of anti-corona filling glue Conclusion: The anti-corona glue with the addition of nano-SiO2 improves the insulation performance of the binding structure at the winding end of the hydropower unit.
[0071] 3.4 Partial discharge detection Detection method: The test method is carried out in accordance with IEC-270, with test conditions at altitudes of 2500m, 3000m, 3500m and 4000m, and test temperatures of 0℃ and 30℃. At high altitudes, the air density is lower, so the air is more easily broken down to cause corona discharge. In this experiment, partial discharge exceeding 10,000 pF is considered to be the start of discharge. The results are shown in Tables 5 and 6.
[0072] Table 5 Partial discharge at 0℃ Table 6 Partial discharge at 30℃ Conclusion: The results show that the anti-corona glue of sample 5 significantly reduces the amount of partial discharge compared with the anti-corona glue of the control sample, whether at 0℃ or 30℃. In particular, when the test voltage is 1Un, the control group is close to 10000pF at only 2500m, indicating that discharge is about to begin. Sample 5 can still maintain no discharge at an altitude of 3500m at 0℃, and maintain no discharge at an altitude of 4000m at 30℃.
[0073] 3.5 Corona inception voltage detection Detection method: The test method is carried out in accordance with "DL / T 298-2011 Guidelines for Corona Detection and Assessment of Generator Stator Winding Ends", and the detection is carried out using an ultraviolet imager. The voltage when the photon number exceeds 1500 is regarded as the corona inception voltage. The test conditions are 2500m, 3000m, 3500m and 4000m above sea level, and the test temperature is 0℃ and 30℃. The results are shown in Tables 7 and 8.
[0074] Table 7 Corona onset voltage at 0℃ Table 8 Corona onset voltage at 30℃ Conclusion: Compared with the anti-corona glue of the control sample, the anti-corona glue of sample 5 increases the corona inception voltage at the binding structure of the winding end of the hydropower unit and improves its anti-corona performance under high altitude conditions.
[0075] The embodiments of the present invention are described above in conjunction with the accompanying drawings, but the present invention is not limited to the above-mentioned specific implementation methods. The above-mentioned specific implementation methods are merely illustrative and not restrictive. Under the enlightenment of the present invention, ordinary technicians in this field can also make many forms without departing from the scope of protection of the purpose of the present invention and the claims, which all fall within the protection of the present invention.
Claims
1. An anti-corona filling glue with low relative dielectric constant, characterized in that: The anti-corona filling glue is prepared by mixing an epoxy adhesive and a filler. The epoxy adhesive includes a component A and a component B. The filler is nano-SiO2 powder. The nano-SiO2 powder is cross-linked with the epoxy adhesive component A. The epoxy adhesive component A is a bisphenol A type epoxy resin. The epoxy adhesive component B includes a composite curing agent and a diluent. The composite curing agent includes polyamide, phenolic amine, 2,4,6-tris (dimethylaminomethyl) phenol. The diluent is resorcinol diglycidyl ether; the mass ratio of each substance in the epoxy adhesive component B is 35-40:9-14:4-9:12-17 of polyamide:phenol aldehyde amine:2,4,6-tris (dimethylaminomethyl) phenol:diluent; the mass ratio of the epoxy adhesive component A to the epoxy adhesive component B includes 10:3, 3:1.5 or 3:2; the viscosity range of the colloid made of the epoxy adhesive component A and the B component is 180-380 mPa·s; the weight percentage of the nano-SiO2 powder in the epoxy adhesive is 1%-3%.
2. The anti-corona filling glue with low relative dielectric constant as claimed in claim 1, characterized in that: The weight percentage of the nano-SiO2 powder in the epoxy adhesive includes 1%, 1.5%, 2%, 2.5% or 3%.
3. The anti-corona filling glue with low relative dielectric constant as claimed in claim 1, characterized in that: The mass ratio of the epoxy adhesive component A to the epoxy adhesive component B is 10:
3.
4. The anti-corona filling glue with low relative dielectric constant as claimed in claim 1, characterized in that: The mass ratio of each substance in the epoxy adhesive component B is 35:9:4:12: polyamide:phenol amine:2,4,6-tris(dimethylaminomethyl)phenol:diluent.
5. The anti-corona filling glue with low relative dielectric constant according to claim 1, characterized in that: The particle size of the nano-SiO2 powder is in the range of 7-40 nm.
6. The anti-corona filling glue with low relative dielectric constant as claimed in claim 1, characterized in that: The specific surface area of the nano-SiO2 powder is 120 m 2 / g.
7. The method for preparing the anti-corona filling glue with low relative dielectric constant according to any one of claims 1 to 6, characterized in that: The following steps are involved: S01: Mix the nano-SiO2 powder and the epoxy adhesive component A and stir evenly to obtain a first mixed solution; S02: adding the epoxy adhesive component B to the first mixed solution and stirring evenly to obtain a second mixed solution, wherein the mass ratio of the epoxy adhesive component A to the epoxy adhesive component B includes 10:3, 2:1 or 3:2; and the weight percentage of the nano-SiO2 powder in the epoxy adhesive is 1%-3%; S03: placing the second mixed liquid in a vacuum drying environment, vacuuming to remove bubbles at room temperature, and then curing to obtain the anti-corona filling glue with a low relative dielectric constant.
8. The preparation method according to claim 7, characterized in that: In the S01, the nano-SiO2 powder and the epoxy adhesive component A are magnetically stirred at 60-80°C for 0.5-1h, and ultrasonically shaken to mix the components evenly.
9. The preparation method according to claim 7, characterized in that: In the S02, the epoxy adhesive component B is added to the first mixed solution and magnetically stirred at room temperature for 10-15 minutes to obtain the second mixed solution.
Citation Information
Patent Citations
Electrical insulating epoxy resin composition and preparation method thereof
CN104479294A
Underfill adhesive suitable for 5G equipment chip packaging and preparation method thereof
CN113122172A
Epoxy resin composition and resin molding using the same
EP0676448A1
Nano-composite dielectrics
WO2008000104A1